Serological and molecular detection of Theileria equi in sport horses of northeastern Brazil. (August 2016) - Ferreira, Edlainne P.; Vidotto, Odilon; Almeida, Jonatas C.; Ribeiro, Luana P.S.; Borges, Marcos V.; Pequeno, Walter H.C.; Stipp, Danilo T.; de Oliveira, Celso J.B.; Biondo, Alexander W.; Vieira, Thállitha S.W.J.; Vieira, Rafael F.C.
Highlights: First study to combine serological and molecular detection of T. equi in sport horses from Brazil. Potential risk factors for exposure/infection by this protozoa were evaluated. Detection of T. equi DNA and sequencing of the EMA-1 gene confirmed infection. Anemia and hyperproteinemia were not associated with infection. Abstract: Theileriosis is a worldwide protozoal tick-borne disease caused by Theileria equi, which may produce a variety of clinical signs and turn infected horses into lifetime carriers. This study has aimed to perform a serological and molecular detection of T. equi and associated factors in sports horses from six areas of northeastern Brazil. In overall, 59.6% horses were positive by indirect immunofluorescence assay and 50.4% by polymerase chain reaction. No significant association was found when presence of ticks, age, gender, anemia or total plasma proteins was analyzed with seropositivity and molecular techniques. Although a significant association of infection was found in two cities. Thus, local risk factors other than presence of ticks, horse age, gender, anemia and total plasmatic proteins may dictate prevalence of T. equi infection in sports horses, even in highly endemic areas with no control of infection prior to horse competitions.